The Accuracy of Preoperative Imaging in The Detection of Gallbladder Carcinoma - Saeed Nadhim Younis (Diyala Journal of Medicine, 2019)
Introduction: Primary carcinoma of the gallbladder is an uncommon, aggressive malignancy that affects women more frequently than men. Older age groups are most often affected, and coexisting gallstones are present in the vast majority of cases. The symptoms at presentation are vague and are most often related to adjacent organ invasion, and the radiologic findings in early-stage cancers are subtle and may mimic those of acute or chronic cholecystitis and many gallbladder carcinomas are diagnosed in an advanced stage ,therefore, despite advances in cross-sectional imaging, early-stage tumors are not often encountered.